On-farm practices associated with multi-drug-resistant escherichia coli and vibrio parahaemolyticus derived from cultured fish - Rita Rosmala Dewi; Hassan, Latiffah; Mohammad Daud, Hassan; Matori, Mohd. Fuad; Zakaria, Zunita; Ahmad, Nur Indah; A. Aziz, Saleha; Mohammed Jajere, Saleh (MDPI AG, 2022)
Aquaculture activities have been implicated as responsible for the emergence of antimicrobial resistance (AMR), leading to broad dissemination and transference of antibiotic resistance to pathogens that affect humans and animals. The current study investigates the on-farm practices and environmental risk factors that can potentially drive the development and emergence of multi-drug-resistant (MDR) Escherichia coli and Vibrio parahaemolyticus in the aquaculture system. A cross-sectional study was conducted on 19 red hybrid tilapia (Oreochromis spp.) and 13 Asian seabass (Lates calcarifer, Bloch 1970) farms on the west coast of peninsular Malaysia. Data were collected using a structured questionnaire pertaining to farm demography, on-farm management practices and environmental characteristics. Multi-drug-resistant E. coli (n = 249) and V. parahaemolyticus (n = 162) isolates were analyzed using multi-level binary logistic regression to identify important drivers for the occurrence and proliferation of the MDR bacteria. On-farm practices such as manuring the pond (OR = 4.5; 95% CI = 1.21–16.57) were significantly associated with the occurrence of MDR E. coli, while earthen ponds (OR = 8.2; 95% CI = 1.47–45.2) and human activity adjacent to the farm (OR = 4.6; 95% CI = 0.75–27.98) were associated with an increased likelihood of MDR V. parahaemolyticus. Considering the paucity of information on the drivers of AMR in the aquaculture production in this region, these findings indicate the targeted interventions implementable at aquaculture farms to efficiently abate the risk of MDR amongst bacteria that affect fish that are of public health importance.